Crises financeiras na primeira década republicana e os bancos em Minas Gerais (1889-1903) - Marcus Antonio Croce (2013)
The transition from slavery to free labor in Brazil (1888-1889) provoked the enactment of a new economic policy with an expansionist style. With abundant supply of credit and greater issuance of cash, a highly speculative situation took placeinthe city of Rio de Janeiro, the country's financial center duringthis period of time. This speculative situation, known as the Encilhamento Crisis, began in a euphoric periodstill inthe Empireera andbroke out in the early years of the Republic (1891), and lasted for a whole decade. The Brazilian financial market was severely hit by this financial crisis, resulting on the bankruptcy of several financial institutions, leading to a situation where a very short number of financial institutions were still operating after the year of 1900. The same happened to the banks operating inMinas Gerais, once they were deeply involved in this juncture. Only one exception, the Credit Real Bank of Minas Gerais stood on its feet through out the Encilhamento Crisis, and, between 1896 and1909 no banking establishment was opened in that State. In 1903, in the city of Belo Horizonte, took place the Agricultural, Industrial and Commercial Congress ofMinas Gerais. The thesis presented in this meeting, in order to diagnose and come up with solutions forthe negative picture that the states economy was going through, generated the new drivers of a new dynamic for the financial sector of Minas Gerais.